H626R and R124C mutations of the TGFBI (BIGH3) gene caused lattice corneal dystrophy in Vietnamese people. Issue 6 (1st June 2003) - Chau, H M; Ha, N T; Cung, L X; Thanh, T K; Fujiki, K; Murakami, A; Kanai, A
Abstract : Background/aims: Mutations of the human transforming growth factor β induced gene ( TGFBI ) were reported to cause lattice corneal dystrophy (LCD) in various nationalities. This study analysed the TGFBI gene in Vietnamese people with LCD. Methods: 13 unrelated families, including 34 patients and 21 unaffected members were examined. 50 normal Vietnamese people served as controls. Blood samples were collected. Genomic DNA was extracted from leucocytes. Analysis of TGFBI gene was performed using the polymerase chain reaction and direct sequencing. Corneal buttons were studied histopathologically. Results: Two clinically distinguishable forms of LCD were revealed: one was typical of LCDI; the other was characterised by the late onset, thick lattice lines, and asymmetry between two eyes. Sequencing of the TGFBI gene revealed R124C mutation in three families and H626R mutation in 10 families. Congo red staining of the H626R-LCD cornea showed amyloid deposits in the subepithelial and stromal layers. Conclusions: R124C and H626R mutations of TGFBI gene caused LCD in Vietnamese people. R124C, a common cause of LCDI in many nationalities, was relatively rare, whereas H626R reported in several white people but not yet in Asians was most common (>75%) in Vietnamese people. Since the phenotype caused by H626R represents a new variant intermediate between LCDI and LCDIIIA, we proposed to consider it as LCD type IIIB.